2, 5-Hexanedione induced apoptosis in rat spinal cord neurons and VSC4.1 cells via the proNGF/p75NTR and JNK pathways. Issue 4 (30th April 2021) - Luo, Mengxin; Shi, Xiaoxia; Guo, Qi; Li, Shuangyue; Zhang, Qing; Sun, Xiuyan; Piao, Fengyuan
Abstract: Increasing evidence suggests that n -hexane induces nerve injury via neuronal apoptosis induced by its active metabolite 2, 5-hexanedione (HD). However, the underlying mechanism remains unknown. Studies have confirmed that pro-nerve growth factor (proNGF), a precursor of mature nerve growth factor (mNGF), might activate apoptotic signaling by binding to p75 neurotrophin receptor (p75NTR) in neurons. Therefore, we studied the mechanism of the proNGF/p75NTR pathway in HD-induced neuronal apoptosis. Sprague–Dawley (SD) rats were injected with 400 mg/kg HD once a day for 5 weeks, and VSC4.1 cells were treated with 10, 20, and 40 mM HD in vitro . Results showed that HD effectively induced neuronal apoptosis. Moreover, it up-regulated proNGF and p75NTR levels, activated c-Jun N-terminal kinase (JNK) and c-Jun, and disrupted the balance between B-cell lymphoma-2 (Bcl-2) and Bcl-2-associated X protein (Bax). Our findings revealed that the proNGF/p75NTR signaling pathway was involved in HD-induced neuronal apoptosis; it can serve as a theoretical basis for further exploration of the neurotoxic mechanisms of HD.